TEKNOLOGI BARU MEDIA DAN DEMOKRATISASI DI INDONESIA - Holik, Idham (Fakultas Komunikasi, Sastra, dan Bahasa, 2010)
New media has transformed the politics of Indonesia from authoritarian regime to democratic regime. In the New Order, it was used as a channel for the consolidation of political movement to fight the Order. Finally in Mei 20, 1998, the movement succeeded to steping down Soeharto as the President. So, Indonesia has entered a new era of politics where the wave of democratization begins. In the democratic era, new media has been able to increase the quality of political participation where the people are more active in the public sphere and the political communication is more interactive. The political participation is the biggest political capital for the state in developing the democratic political life to be mature. Actually, the political potential is not fully supported by the democratic cyber regulation of new media . It is a threat for the future of democracy in Indonesia